Modernity, Generations, and the Assimilation of Thomas Jefferson’s Indians - Vajda, Zoltán (AMERICANA E-journal of American Studies in Hungary, 2019)
This paper offers an analysis of Thomas Jefferson’s ideas about generations with regard to Native Americans within a broader intellectual context. Informed by the Enlightenment view of generations as discreet units of a given population Jefferson thought of them as isolated entities, each taking a possibly distinct place in the process of rational development and civilization. Their isolation implying difference from the “parental stock,” he also regarded them as being in an antagonistic relationship with one another, equalling the distinct status of a nation. I argue that understanding of the generational divide proved crucial in Jefferson’s assessment of Native American cultures and their capacity for change and assimilation into white American society. His plans to break generational ties within Native American cultures was an integral part of his project to bring them under the power of modern rational time as well as to achieve such a change gradually, thus leaving parents (i.e. older generations) behind. Aware of the Native Americans’ generational model being different from the modern European one, he took serious efforts to impose his own model of generations upon them by calling for an epistemological revolution among them, promoting their assimilation.